My phone, my zone: Restaurant consumers' territorial responses to unsolicited recommendation on their smartphones. (February 2022) - Tang, Yangyi (Eric); Yang, Liu; He, Yuanqiong
Abstract: In the past few years, an increasing number of restaurants have integrated self-service technology. Consumers today can engage in self-service using devices that restaurants provide onsite or their smartphones to access the restaurants' online systems. Yet, limited research exists on the influence of interacting with different self-service devices on consumer behavior. The present research investigated the effect of self-service device type on consumers' territorial behavior through four scenario-based experiments. Specifically, when consumers use their smartphones (vs. using the ordering devices provided by the restaurants) to order food, their compliance with restaurants' unsolicited food recommendations decreased (Studies 1a and 1b) because consumers perceived those recommendations as infringements on their ordering process (Study 2). Moreover, consumers' familiarity with restaurants' environments moderated this effect (Study 3). Our findings add to the research on self-service and consumer territoriality and provide practical implications for marketers. Highlights: The type of self-service devices influences consumers' perceived territoriality. Smartphone ordering reduces consumers' compliance with unsolicited recommendations. Consumers' familiarity with restaurant environment alleviates the proposed effect.